Comparison between Carboxy Methyl Cellulose and Carbomer as Viscosity Agents on the Physical Stability of Combination Shampoo Preparations of Jackfruit Leaves (Artocarpus heterophyllus) and Pandan Leaves (Pandanus amarillyfolius) - Rosaria Ika Pratiwi; Aish Fitriani; Febrilliani (Universitas Negeri Medan, 2025)
Viscosity agents such as carboxy methyl cellulose (CMC) and carbomer are an important part of shampoo preparations because they function as regulators of the viscosity of the preparation which can affect physical stability. This study analyzes the differences between CMC and carbomer as viscosity agents on the physical stability of a combination shampoo preparation of jackfruit leaves (Artocarpus heterophyllus) and pandan leaves (Pandanus amarillyfolius). The physical stability measured by this shampoo preparation includes the density test, viscosity test, and foam test. There is a difference in specific gravity between shampoos that use the viscosity agent CMC and carbomer in F1, F2, and F3 (P value <0.05), a difference in viscosity in F1 (P value <0.05), and there is no difference in viscosity between the shampoos used. using viscosity agent CMC with carbomer on F2 and F3 (P value >0.05), as well as high foam on F1, F2, and F3 (P value >0.05).